PERUBAHAN SOSIAL DALAM PELAKSANAAN ADAT PERKAWINAN SUKU JAWADI LOKASI TRASMIGRASI DESA PASIR UTAMA KABUPATEN ROKAN HULU - Riska Ayufatmala; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Indonesian people are people who consist of many ethnic and culture. National cultural is cultural who rise from cultivation’s work from Indonesian people in all of subject. People are person who life together and make a cultivation. Altogether, nothing people who haven’t culture and nothing cultural without the people to be the container and supporter too. Technology advancement not only bring the changes on sector fisic development, but to changes the siclus of family’s life, who start from the birth and finish with dead. The change must appropriate with each of the rule. Mating is part from human’s life siclus who interested enought to studied, especially the changes who happen and have tight related with family establishment. The Pasir’s Villager seen more focus to balanching the mobilization movement and the social changes was happened. Not only on the People but from other people beyond too. The changes who seen in Pasir Utama’s villager is in implementation Java’s ethnic mating tradition. Long ago the implementation did in phases. But now the tradition begin leaved and the part not arranged. Now the mating ceremony more direct to completely implementation. Reshuffle and changes happen in the system mothod of mating tradition who happen for many factor amongst of another culture contact, education’s level, income’s level and geographical factor.Key word: social changes, ethnic, marriage.